Histomorphometric Study on the Effects of Methotrexate on Gonads: An Experimental Study in Albino Rat - Tandon, Rati; Rahman, Nusra; Moinuddin, Arsalan; Gaur, Mudrika; Battan, Gulshan; Faruqi, Nafis Ahmad (Academia Anatomica International, 2017)
Background: Prolonged use of methotrexate in juvenile arthritis and multisystem involvement due to its toxicity prompted us to find out detailed histo-morphometric study after exposure to drug. The concern became alarming because of reported gonadal damage due its direct effect on fertility. Methods: Methotrexate was injected in both male and female rats (1mg/kg, intraperitoneally), weekly for 6 weeks. Thin sections of testis and ovary of both control and experimental groups were stained with H/E stains for light microscopic examination. Results: Histo-morphometric observations on seminiferous tubules included, external diameter, thickness of the wall and the diameter of the lumen. Such observations for ovarian tissue included diameters of ovarian follicles and their ova. Highly significant changes in both testicular and ovarian microscopic parameters confirmed the damage of tissue in experimental groups. Conclusion: The study suggests that utmost precaution should be taken while using methotrexate in younger patients. Conclusion: The results will aid the clinician in choosing an appropriate muscle and tendon lengths in surgeries. This definitely will lead to better functional and aesthetic outcomes in restorative procedures.